A harmonized dataset relating alternative farmer management practices to crop yield, soil organic carbon stock, nitrous oxide emissions, and nitrate leaching generated using IPCC methodologies and meta-analysesZenodo - Roberta Calone; Angela Fiore; Guido Pellis; Maria Luz Cayuela; Gabriele Mongiano; Alessandra Lagomarsino; Simone Bregaglio (Data in Brief)
Farming practices such as soil tillage, organic/mineral fertilization, irrigation, crop selection and residues management influence multiple ecosystem services provided by agricultural systems. These practices exhibit complex, non-linear interrelationships that affect crop productivity, water quality, and non-carbon dioxide greenhouse gases (GHG) emissions, possibly offsetting their benefits regarding soil organic carbon (SOC) sequestration. Current methodologies from the Intergovernmental Panel on Climate Change (IPCC) forassessing the impacts of alternative farming practices on GHG emissions rely on global or country-specific coefficients. However, these methods often do not explicitly account for the combined effects of management practices on carbon and nitrogen cycles or productivity, as this is not required for national GHG inventories. Here we present a new dataset featuring 1.8 Mln of agronomic case scenarios, i.e., unique combinations of farming practices and pedoclimatic conditions, which have been associated with values of SOC changes, nitrous oxide emissions, nitrate-nitrogen leaching, and crop yield. To synthesize trade-offs and synergies between farming practices, each case scenario has been ranked with a ∑ommit index (∑i) value, a fuzzy-based measure ranging from 0 (bad) to 1 (good). The four trade-off components have been estimated by combining available information from i) the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, ii) the guidelines for Green Water Footprint Accounting, iii) the Italian National Institute of Statistics, iv) and other international meta-analytic studies. The dataset presents four ∑i series, corresponding to alternative perceptions of sustainability from three potential stakeholder categories (young farmers’ cooperative, agrochemical company, public agricultural policy agency) plus one equally weighted option. By providing a harmonized data source and an innovative metric, this dataset allows users to explore trade-offs associated with alternative management practices across four key agricultural components and assess their impact on perceived agroecosystem sustainability.